2017
DOI: 10.3390/su9081362
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations and Numerical Simulation of Thermal Performance of a Horizontal Slinky-Coil Ground Heat Exchanger

Abstract: Abstract:A model test system of horizontal slinky coil ground heat exchanger (HSCGHE) was established according to the similarity theory. A 2-D mathematical model of HSCGHE was built and experimentally validated. Experimental and numerical investigations of effects of different parameters on the thermal behavior of HSCGHE were undertaken. The results show that the heat release rate of the slinky coil and soil temperature around it increase as the inlet fluid temperature of coil increases. The soil temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The intermittent operation mode is regarded as an effective approach to mitigate thermal imbalance risk. Zhang et al [22] conducted experimental and numerical study of thermal performance of a horizontal slinky-coil ground heat exchanger and concluded that the soil temperature operated in intermittent mode can get a recovery, and thus, the heat release rate of the coil can be improved. Wang et al [23] simulated and studied the heat exchange performance of PCM-backfilled buried pipes under intermittent operation in summer, and the results showed that the PCM with low phase change temperature could significantly improve the heat exchange rate of the buried pipes at the early stage of intermittent operation.…”
Section: Introductionmentioning
confidence: 99%
“…The intermittent operation mode is regarded as an effective approach to mitigate thermal imbalance risk. Zhang et al [22] conducted experimental and numerical study of thermal performance of a horizontal slinky-coil ground heat exchanger and concluded that the soil temperature operated in intermittent mode can get a recovery, and thus, the heat release rate of the coil can be improved. Wang et al [23] simulated and studied the heat exchange performance of PCM-backfilled buried pipes under intermittent operation in summer, and the results showed that the PCM with low phase change temperature could significantly improve the heat exchange rate of the buried pipes at the early stage of intermittent operation.…”
Section: Introductionmentioning
confidence: 99%
“…condensing temperature and evaporating temperature) can be optimised from the knowledge of the ideal IR which in turn increases the efficiency of the GSHP system [26]. The mean heat exchange rate of a GHE is higher in intermittent operation compared to continuous operation which makes it more efficient with regards to energy performance and soil temperature variation [27][28][29][30][31][32][33]. For soil with high thermal conductivity the rate of soil thermal recovery increases during intermittent operation, which improves the performance of the GHE [34].…”
Section: Introductionmentioning
confidence: 99%